Affective Outcomes of Membership in a Sport Fan Community - Mastromartino, Brandon; Zhang, James J. (Frontiers in Psychology, 2020)
In this mini-review, we shed light on the important, yet under researched topic area in sport management – understanding the role that emotion plays for members of sport fan communities. Much research has been done on the relationship between sport organization and fan; yet, far more needs to be discussed on how the sense of community fans feel lead to affective outcomes and consumption behaviors. With an understanding of the affective outcomes resulting from a connection between fans, sport organizations can use the knowledge to develop promotional procedures and nurture their fan community in an effort to grow their fan base and elevate consumption behavior. The aim of this mini-review is to (a) draw attention to the value of sport fan communities and (b) highlight areas in which sport organizations can build marketing strategies. As it is necessary for sport organizations to better understand the role emotion plays in the consumer behavior of their fans, more attention needs to be paid in understanding the affective benefits of membership in a sport fan community.